]{Psycho-Pedagogical Foundations of Professional and Personal Development of Students in the Process of Professional Training in Higher Educational Institutions - Yurii Moseichuk (Pedagogical Discourse, 2017)
During the research the existence of an essential interest of pedagogues and psychologists to the problem of personal and professional development of the individual and the formation of professional tops was established. It was found that personal development occurs in the activity that is subject to the system of reasons of this person. From a psychological point of view development is understood as the changes in consciousness and human behavior, which cover the emergence of new motives and interests. So, development is the main way of existence of person. Future specialist during the study in higher educational institutions must develop personal qualities such as wide erudition, strategic thinking, adventurousness, high culture. The main focus is on the analysis (psychological, pedagogical and acmeological) of scientific definition of «professional development». Psychologists consider professional development as the development of the individual in the process of selecting occupation, vocational education and training and productive performance of professional activities. From a psychological position it was found that the development of a professional is the result of: a systematic improvement, the expansion and reinforcement of the range of its theoretical knowledge; the development of personal qualities; the improving of arsenal of practical skills. The authors of acmeological concepts of professional development prove that the professionalism of the individual is achieved during the formation of professionally important skills, the development of personal and professional qualities, the enriching of moral world, reflective culture, creativitive and innovative potential. In pedagogical context the professional development of the individual is provided by education, training, self-education, pedagogical support, correction, organized socialization. On the basis of researchers’ works it was found that a professional development is a process of the resolving of professionally important tasks (cognitive, communicative, moral) when a specialist masters the necessary range of business and moral qualities.The basic principles of the professional development of pedagogues which aims at the formation of teachers’ ability to acquire qualities, knowledge and skills necessary for successful acivity were developed. In the course of theoretical and methodological analysis the views of foreign scholars on the essence and content of the professional development of teachers were highlighted. Key words: development, personal development, professional development, professional pedagogue’s development.